(untitled) (Academia Journal of Medicine, 2026)
Oral cancer, predominantly oral squamous cell carcinoma (OSCC), remains a major global health burden with high morbidity and mortality rates. Traditional two-dimensional (2D) cell cultures and animal models often fail to accurately replicate tumor heterogeneity and the complex tumor microenvironment. Organoids, three-dimensional (3D) in vitro culture systems derived from stem cells or tumor tissues, have emerged as a revolutionary tool in cancer research. Oral cancer organoids closely mimic the histological architecture, genetic profile, and functional characteristics of the original tumor. This review discusses the concept, development, methodologies, and applications of organoids in oral cancer research, highlighting their role in disease modeling, drug screening, and personalized medicine. Additionally, limitations, challenges, and future prospects are addressed.